ANALISIS IMPLEMENTASI KEBIJAKAN PUBLIK PENGELOLAAN SAMPAH REFUSED DERIVED FUEL (RDF) DI KABUPATEN CILACAP - Syamsul Auliya Rachman; Muchlis Hamdi; Aries Djaenuri; Ika Sartika (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2020)
As an industrial area and a large population, it certainly causes various kinds of problems, namely waste, population growth will be directly proportional to the increase in the amount of waste. Cilacap Regency has made waste management innovations with Refused Derived Fuel (RDF) technology, which turns waste into alternative fuel to replace coal. In this paper the writer tries to analyze it with a descriptive design with a qualitative approach. Writing informants were determined by purposive sampling. The theoretical basis used is the Van Metter and Van Horn theory approach because it is more appropriate to the conditions of implementing the waste management policy. The results of this paper indicate that the implementation of RDF's waste management public policy is not running optimally. The main factor is the financial resources and the various parties involved which actually make it less optimal and not on time due to the communication factor.